SUMMARY OF EXPENSES AS ECONOMIC AND ACCOUNTING ANALYTICAL CATEGORIES - F. Haloul (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The evolution of the interpretation of the term “cost” is shown understanding of the essence of categories “costs”, “expenses”, “production costs” as the representatives of ancient philosophy, and representatives of various economic trends: classical political economy, Marxist theory, neoclassical, institutionalism and neo-institutionalism. Ukrainian scientists studied approaches to disclosure, costs and expenses. Approaches different authors, scientists and economists to the definition of “costs” and “expenses”. Studied the definition of “costs” and “expenses” in Ukrainian and foreign regulatory literature. Showing features researched categories. Valid conclusions about the absence of synonymy between the terms “costs” and “expenses” as the accounting and analytical, financial and economic categories, respectively. The author ‘s definition of the terms “costs” and “expenses”.